Elevated serum levels of Chromogranin A in hepatocellular carcinoma - Biondi, Antonio (BioMed Central, 2012)
BACKGROUND: During the past three decades, the incidence of hepatocellular carcinoma in the United States has tripled. The neuroendocrine character has been observed in some tumor cells within some hepatocellular carcinoma nodules and elevated serum chromogranin A also been reported in patients with hepatocellular carcinoma. The aim of this work was to investigate the role of serum concentration of chromogranin A in patients with hepatocellular carcinoma at different stages. METHODS: The study population consisted of 96 patients (63 males and 33 females age range 52-84) at their first hospital admission for hepatocellular carcinoma. The control group consisted of 35 volunteers (20 males and 15 females age range 50-80). The hepatocellular carcinoma patients were stratified according the Barcelona-Clinic Liver Cancer classification. Venous blood samples were collected before treatment from each patients before surgery, centrifuged to obtain serum samples and stored at -80° C until assayed. RESULTS: The chromogranin A serum levels were elevated (> 100 ng/ml) in 72/96 patients with hepatocellular carcinoma. The serum levels of chromogranin A were significantly correlated (p<0.05) with alpha-fetoprotein. In comparison with controls, the hepatocellular carcinoma patients showed a significant increase (p<0.001) vs controls. The chromogranin A levels in the Barcelona staging of hepatocellular carcinoma was higher in stage D compared to stage C (p<0.01), to stage B (p<0.001), and to stage A (p<0.001). CONCLUSIONS: Molecular markers, such as chromogranin A, could be very useful tools for hepatocellular carcinoma diagnosis. However the molecular classification should be incorporated into a staging scheme, which effectively separated patients into groups with homogeneous prognosis and response to treatment, and thus serves to aid in the selection of appropriate therapy.